The Relation between Type One Diabetes Mellitus and Occurrence of Celiac Disease in Patients with in Babylon Teaching Hospital for Maternity and Children - Hakim yousif Radi; Yahya A. Altufaily; Ali Sami Mohammed (Indian Journal of Forensic Medicine & Toxicology, 2021)
Although the association between type 1 diabetes mellitus and celiac disease is well known, the presentingfeatures and clinical characteristics of the two diseases, when they coexist, are less well documented sothe study aimed to Estimate the incidence of celiac disease among patients attended to diabetic clinic inthe Babylon maternity and pediatric teaching hospital. Include retrospective study involves patients withT1DM attending the pediatric diabetic clinic in the Babylon maternity and pediatric teaching hospital, werescreened for celiac disease by serological testing for celiac antibodies (tissue transglutaminase). Controlgroup without diabetes mellitus were also been evaluated. The control group are those who were admitted tothe hospital for other diseases like gastroenteritis or chest infection, have no past medical history or chronicillnesses, and have no diabetes mellitus neither symptoms nor abnormal blood investigation results. Of the50 patients with T1DM and 50 without diabetes mellitus, 3 patients (6%) of the study group tested wereantibody positive. Celiac disease presented atypically in the majority of cases with an unpredictable intervalbetween diagnosis of diabetes and celiac disease presentation. In this study, we found that patients withclassical symptoms of celiac disease, (diarrhea, anorexia, abdominal distension, foul smelling stool, shortstature, unexplained hypochromic anemia), may have negative screening for celiac disease, while those withpositive screening test, were asymtomatic.